2001
DOI: 10.1093/ajcn/73.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an integrated nutrition curriculum on medical education, student clinical performance, and student perception of medical-nutrition training

Abstract: Medical students improved their clinical nutrition practice skills through participation in an integrated nutrition curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 24 publications
0
35
2
Order By: Relevance
“…Those involving professionals were generally shorter. The shortest intervention was a 1-hour intensive session for GPs and other healthcare professionals on the benefits of giving folic acid to women of child bearing age;52 the longest were two 4-year integrated nutrition curricula for medical students 3551 Inconsistent reporting of the length of interventions (including use of terms like credit hours) made it difficult to determine their average lengths.…”
Section: Resultsmentioning
confidence: 99%
“…Those involving professionals were generally shorter. The shortest intervention was a 1-hour intensive session for GPs and other healthcare professionals on the benefits of giving folic acid to women of child bearing age;52 the longest were two 4-year integrated nutrition curricula for medical students 3551 Inconsistent reporting of the length of interventions (including use of terms like credit hours) made it difficult to determine their average lengths.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative, nutrition education has been incorporated into all four years of medical education at a number of institutions [23,24]. Preliminary evaluation of this approach suggests that students became knowledgeable about nutrition and were better able to address the nutritional needs of their patients than their counterparts in a traditional curriculum [24].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, at least 1 school has reported that an integrated nutrition curriculum greatly increased the total hours of instruction and improved Objective Structured Clinical Examination (OSCE) nutrition scores and student satisfaction with nutrition instruction. 24 …”
Section: Nutrition Instruction In Medical School and Residency Programsmentioning
confidence: 99%